Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0183552
|View full text |Cite
|
Sign up to set email alerts
|

The aggressiveness of neurotrauma practitioners and the influence of the IMPACT prognostic calculator

Abstract: Published guidelines have helped to standardize the care of patients with traumatic brain injury; however, there remains substantial variation in the decision to pursue or withhold aggressive care. The International Mission for Prognosis and Analysis of Clinical Trials in TBI (IMPACT) prognostic calculator offers the opportunity to study and decrease variability in physician aggressiveness. The authors wish to understand how IMPACT’s prognostic calculations currently influence patient care and to better unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…Treatment options for TBI patients are scarce, and documenting prognosis in the intensive care setting does not seem to substantially affect treatment decisions. [25][26][27] On the other hand, there is an increasing recognition that estimates of prognosis by clinicians are often unduly pessimistic for TBI patients, 28 and regular comparison of outcome predicted by these models with clinical expectations may help individual clinicians calibrate their prognostication and practice. Based on the good discriminative ability of the IMPACT and CRASH models, potential applications in research settings are risk stratification in trials and covariate adjustment in statistical analyses to increase statistical power.…”
Section: Figmentioning
confidence: 99%
“…Treatment options for TBI patients are scarce, and documenting prognosis in the intensive care setting does not seem to substantially affect treatment decisions. [25][26][27] On the other hand, there is an increasing recognition that estimates of prognosis by clinicians are often unduly pessimistic for TBI patients, 28 and regular comparison of outcome predicted by these models with clinical expectations may help individual clinicians calibrate their prognostication and practice. Based on the good discriminative ability of the IMPACT and CRASH models, potential applications in research settings are risk stratification in trials and covariate adjustment in statistical analyses to increase statistical power.…”
Section: Figmentioning
confidence: 99%
“…In the first patient scenario, belief about the patient's prognosis was associated with the decision to offer or not offer a craniotomy. In a previous study, neurosurgeons stated they would consider not offering aggressive treatment when the chance of specific poor prognoses was 80% or greater [15]. Interestingly, in our study, although poor prognosis correlated with fewer craniotomies, many neurosurgeons were still willing to recommend craniotomy at a very low chance of functional recovery.…”
Section: Plos Onementioning
confidence: 40%
“…due to the fact that neurosurgeons are not confident in the validity of the tool, that they have fixed beliefs about prognosis, or that they primarily rely on personal experience and training to make decisions. Indeed, a recent survey of neurosurgeons found that the use of risk calculators is rare in practice, and that neurosurgeons are unlikely to rely on them for decision making [15]. Finally, it is possible that neurosurgeons depending on practice type, experience, or health system in which they practice could have different responses to evidence-based risk estimates.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“… 17–19 Previous work has demonstrated that neurosurgeons tend to be more nihilistic on long-term outcomes than general surgeons or other trauma specialists. 20 In clinical trials in TBI, the leading cause of death is attributable to withdrawal of life-sustaining therapies, often occurring early within 72 h of injury. 21 CRASH and IMPACT lack the discriminatory ability for individual patients to guide life-or-death decisions, given that they incorrectly predicted that nearly 1 in 5 patients would have an unfavorable outcome or die.…”
Section: Discussionmentioning
confidence: 99%